Analisis Dampak Rendahnya Upah Guru terhadap Kualitas Pendidikan di Flores-NTT: Perspektif Hierarki Kebutuhan Abraham Maslow - Felix Riondi Sugar; Marselinus Langgor; Angelbertus Epe Ngore; Antonius M. A. Wangga; Martinus Dampul; Fransiskus Kaka Coo; Fridolin Mawangsuri Fallo (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to analyze the low wages of honorary teachers in Flores, East Nusa Tenggara (NTT), and its impact on the quality of education using Abraham Maslow's hierarchy of needs theory as a perspective. The research employed a descriptive qualitative approach, combining literature review and secondary data analysis from various relevant sources, including government reports, journal articles, and media news. The results indicate that most of the teachers’ basic needs, especially physiological and safety needs, have not been optimally met due to low income and job insecurity. This condition negatively affects teachers’ motivation, professionalism, and teaching quality in schools. While social needs are relatively fulfilled through community support, teachers’ esteem and self-actualization needs remain constrained. Policy disparities, limited facilities, and minimal social protection further exacerbate the situation. The study concludes that the welfare issue of honorary teachers in Flores is a systemic problem that requires serious attention from the government and education stakeholders. The study recommends fairer policy reforms, enhanced teacher welfare, and professional development support to sustainably improve the quality of education.